Identification of potential drug name confusion errors in the Sentinel System. Issue 10 (4th September 2019) - Cocoros, Noelle M.; Haynes, Kevin; Her, Qoua; Cosgrove, Austin; Dee, Elizabeth; Lin, Nancy D.; Tu, Chi‐Ming; Ding, Yulan; Nguyen, Michael; Toh, Sengwee
Abstract: Purpose: In July 2015, the US Food and Drug Administration (FDA) published a drug safety communication regarding errors in prescribing and dispensing of the antidepressant Brintellix (vortioxetine) and the antiplatelet Brilinta (ticagrelor) that arose due to proprietary drug name confusion. Brintellix is indicated for major depressive disorder; Brilinta is indicated to reduce cardiovascular death, myocardial infarction, and stroke in patients with acute coronary syndrome or history of myocardial infarction. Brintellix was renamed to Trintellix in May 2016. Using Brilinta and Brintellix as a proof‐of‐concept feasibility use case, we assessed whether drug name confusion errors between the pair could be identified in electronic health care data via the combination of a claims‐based algorithm and limited manual claims data review. Methods: Using data from the Sentinel System, we defined potential errors as Brintellix users without an on‐ or off‐label indication for Brintellix, without a dispensing for a drug with the same indications as Brintellix, and with an on‐ or off‐label indication for Brilinta between −365 and +30 days after index Brintellix dispensing; the reverse was done for Brilinta. We manually reviewed claims profiles of potential cases. Results: We identified 27 (0.1%) potential errors among 21 208 Brintellix users; 16 appeared to be likely errors based on claims profile review. Fifty‐one (0.3%) of the 16 779 Brilinta users were identified as potential errors, and four appeared to be likely errors. Conclusions: A claims‐based algorithm combined with manual review of claims profiles could identify potential drug name confusion errors, and narrow down likely errors that warrant further investigation.